(untitled) (Research, Society and Development, 2020)
Aiming to rescue the importance of the transmission of knowledge accumulated by humanity as a strategy for the promotion of human emancipation, democracy and social justice, this article presents a synthesis of the personal and professional trajectory of intellectual Anísio Teixeira. Born in 1900 and forgotten by current literature, Anísio Teixeira worked in the Department of Education and Health of the State of Bahia from 1947 to 1951, and promoted significant local and national changes in education. His main struggle was to break with social inequalities and emancipate the future citizen. As a strategy, he supported the New School Movement and created the Park-Schools, these being the first institutions in Brazil to offer teaching in full and emancipation. According to his contributions and his legacy, it is strange for us that his name receives little attention from current educators.